DEVELOPING QUESTIONNAIRE FOR POST GRADUATE STUDIES IN CONSTRUCTION MANAGEMENT - N. Sanda, Yakubu; Natalia A. Anigbogu; Yohana D. Izam; Hannatu L. Datukun (Journal of Surveying, Construction and Property, 2021)
Although questionnaires are widely used in construction management studies, designing the instrument has proven to be a difficult task among research students. This article explored the process of developing and testing questionnaires for construction management studies focusing on managing risks in Public Private Partnership (PPP) housing projects. The processes of developing questionnaire were grouped into four stages consisting of the background, conceptualization, design and instrument testing and administration. Using the processes identified, a flowchart indicating step-by-step stages for developing questionnaires was designed. Results of validity and reliability tests conducted on certain aspects of the questionnaire indicated that the instrument can be relied upon to generate acceptable data for scientific research. The main contribution of this paper is expanding the scope and simplifying the design of questionnaire among upcoming researchers in the field of construction management. This study recommends the design for students undertaking construction management related studies.